Iron-based nanoparticles prepared from yerba mate extract. Synthesis, characterization and use on chromium removal. (1st April 2019) - García, Fabiana E.; Senn, Alejandro M.; Meichtry, Jorge M.; Scott, Thomas B.; Pullin, Huw; Leyva, Ana G.; Halac, Emilia B.; Ramos, Cinthia P.; Sacanell, Joaquín; Mizrahi, M.; Requejo, Félix G.; Litter, Marta I.
Abstract: Iron-based nanoparticles were synthesized by a rapid method at room temperature using yerba mate (YM) extracts with FeCl3 in different proportions. Materials prepared from green tea (GT) extracts were also synthesized for comparison. These materials were thoroughly characterized by chemical analyses, XRD, magnetization, SEM-EDS, TEM-SAED, FTIR, UV–Vis, Raman, Mössbauer and XANES spectroscopies, and BET area analysis. It was concluded that the products are nonmagnetic iron complexes of the components of the extracts. The applicability of the materials for Cr(VI) (300 μM) removal from aqueous solutions at pH 3 using two Cr(VI):Fe molar ratios (MR), 1:3 and 1:0.5, has been tested. At Cr(VI):Fe MR = 1:3, the best YM materials gave complete Cr(VI) removal after two minutes of contact, similar to that obtained with commercial nanoscale zerovalent iron (N25), with dissolved Fe(II), and with a likewise prepared GT material. At a lower Cr(VI):Fe MR (1:0.5), although Cr(VI) removal was not complete after 20 min of reaction, the YM nanoparticles were more efficient than N25, GT nanoparticles and Fe(II) in solution. The results suggest that an optimal Cr(VI):Fe MR ratio could be reached when using the new YM nanoparticles, able to achieve a complete Cr(VI) reduction, and leaving very low Cr and Fe concentrations in the treated solutions. The rapid preparation of the nanoparticles would allow their use in removal of pollutants in soils and groundwater by direct injection of the mixture of precursors. Graphical abstract: Image 1 Highlights: Synthesis of iron-based nanoparticles from yerba mate (YM) extract. Iron-based nanoparticles from YM were completely characterized. YM nanoparticles are nonmagnetic iron complexes of the extract components. Cr(VI) removal higher than with commercial nZVI or green tea nanoparticles.